2015
DOI: 10.1111/1759-7714.12269
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of the invasiveness of lung adenocarcinoma manifesting as ground glass opacities on high‐resolution computed tomography

Abstract: BackgroundTo explore the diagnostic method in assessing the malignancy of pulmonary adenocarcinoma characterized by ground glass opacities (GGO) on computed tomography (CT).MethodsPreoperative CT data for preinvasive and invasive lung adenocarcinomas were analyzed retrospectively. GGO lesions that were detected on lung windows but absent using the mediastinal window were subject to adjustment of the window width, which was reduced with the fixed interval of 100 HU until the lesions were no longer evident, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
(38 reference statements)
2
17
0
Order By: Relevance
“…For a long time, the study of the assessment of GGOs using CT particularly used visual features such as lesion size and the presence of pleural retraction ( 25 ), the proportion of the solid component, the shape and size of the lesion, and the window width ( 26 ). However, it was not an easy or accurate method for identifying the different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, the study of the assessment of GGOs using CT particularly used visual features such as lesion size and the presence of pleural retraction ( 25 ), the proportion of the solid component, the shape and size of the lesion, and the window width ( 26 ). However, it was not an easy or accurate method for identifying the different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported lesion size to be an important predictor for invasiveness in ACs manifesting as pure ground glass nodules [ 19 , 20 ]. Lee et al showed that an overall lesion size of < 10 mm can be used to differentiate between pre-invasive and invasive lesions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…GGO dominant tumors have been increasingly observed due to widespread use of high resolution CT imaging, and many studies have reported a relationship between radiological prognostic factors and pathological invasiveness (9,14,15). The specificity of pathological invasiveness, which is defined as the presence of vascular and lymphatic invasion and lymph node metastasis, was reported to be 100% when the cut-off value was set as a consolidation/maximum tumor ratio of ≤0.5 for lesions ≤3 cm (16).…”
Section: Discussionmentioning
confidence: 99%